Partnering on the PRAISE Program: Putting Health Equity into Practice - Ameena Batada; JeWana Grier-McEachin; Kathey Avery (Mary Ann Liebert, 2017)
Purpose: The purpose of Preventive Health Education Resulting in Action Inspiring Success for Everyone (PRAISE) was to develop a community-driven program to encourage and support churches in sustainable health promotion and assessment efforts to improve African Americans' health knowledge and behaviors in Asheville, North Carolina. Methods: The PRAISE program provided technical support toward gaining recognition and an award for health promotion activities to 10 churches in year 1 and 5 additional churches in year 2. The Results-Based Accountability? (RBA) framework involved documentation of church health promotion activities and surveys of a convenience sample of congregants at nine churches before (presurvey, n=270) and after (postsurvey, n=241) the intervention. Differences in frequency of conduct of and participation in church health promotion activities and in congregant health knowledge and behaviors were assessed in 2015 and 2016. Results: Fourteen of the churches engaged in at least one health promotion activity and more than half offered healthier foods at gatherings, offered exercise opportunities, and held at least three health education activities. Seventy-two percent of congregants reported participating in at least one church health activity at postsurvey compared with 58% at presurvey. The proportion of congregants who had personal health knowledge and the proportion that rated their health as good or better were higher at postsurvey. Conclusion: Building on years of trust and collaboration among churches, local community organizations, and an academic partner, PRAISE in its first 2 years suggests that a community-driven approach can support health promotion and healthy behaviors, advancing health equity efforts.